Perlindungan Konsumen Atas Produk Berbasis Ai : Tantangan Hukum di Era Digital - Melisa Melisa; Habib AlHafiz; Siti Patimah; Marina Juwita; Dini Marissa; Nanda Amelia6; Abdul Halim Nasution (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to examine the legal challenges in consumer protection concerning Artificial Intelligence (AI)-based products in the digital era. Using a literature review method, the research analyzes relevant legal sources such as scholarly journals, legal textbooks, and applicable legislation in Indonesia. The findings reveal that the rapid development of AI technology has not been matched by adequate regulatory frameworks, resulting in several legal issues. These include the absence of specific provisions governing AI service providers' liability, weak personal data protection, and the lack of corrective mechanisms for automated decisions made by AI systems. In this context, consumers are in a vulnerable position due to limited access to algorithmic transparency and data processing procedures. The study emphasizes the need for progressive and responsive legal reform, including the legal recognition of AI as electronic agents, enhanced transparency, and the establishment of robust oversight and accountability systems. Consumer protection in the digital age requires collaborative efforts between regulators, business actors, and civil society to build a fair, secure, and legally just digital ecosystem.